Civil justice reconsidered : toward a less costly, more accessible litigation system - Croley, Steven P., 1965- (New York : New York University Press, 2018)
Prosecutes the civil litigation system and proposes practical reforms to increase access to the courts and reduce costs. Civil litigation has come under fire in recent years. Some critics portray a system of dishonest lawyers and undeserving litigants who prevail too often, and are awarded too much money. Others criticize the civil justice system for being out of reach for many who have suffered real injury. But contrary to these perspectives and popular belief, the civil justice system in the United States is not out of control. Steven Croley demonstrates that civil litigation is, for the most part, socially beneficial.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 7, 2017).
Keywords: Justice, Administration of -- United States; Civil procedure -- United States; Actions and defenses -- United States; Costs (Law) -- United States; Law reform -- United States; Law; United States of America, USA; Systems of law: civil codes / civil law; Laws of specific jurisdictions & specific areas of law; Legal systems: civil procedure, litigation & dispute resolution; Private or civil law: general